DexmedetomidineVersus Clonidine as Adjuvant in Subarachnoid Block in Patients of Preeclampsia Undergoing LSCS. - Varchaswa Pandey; Vibha Mishra; Rahul Gupta (International Journal of Health and Clinical Research, 2021)
Background: The aim of this study is to compare the duration and quality of analgesia with maternal and neonatal outcome following subarachnoid block with intrathecal hyperbaric bupivacaine with either dexmedetomidine or clonidine used as adjuvant in preeclampsia patients undergoing LSCS.Material and Methods: Patients with preeclampsia were drawn from those scheduled for operations requiring subarachnoid block for LSCS.100 ASA grade I & II patients are randomized into two groups.Group A:-Sub arachnoid block with [ 2ml 0.5% Bupivacaine heavy + 45 μg clonidine]Group B:-Subarachnoid block with[ 2ml 0.5% Bupivacaine heavy + 15μg dexmedetomidine]Results: Changes observed in systolic, diastolic and mean blood pressure were comparable in both the groups at different time points (P>0.05). Three patients in Group A and in Group B developed hypotension which responded to intravenous fluid therapy.SpO2 remained stable and comparable in both the groups throughout the study period, (P>0.05).There was significant prolongation of analgesia in Group B where first rescue analgesic was required after 9 hours of subarachnoid blockade. Patients in Group A required rescue analgesic at 7 hours after subarachnoid blockade.There was statistically significant difference in duration of analgesia in two groups. Postoperative analgesia was significantly prolonged in Group B as compared to Group A.Conclusion: Clonidine and Dexmedetomidine as an adjuvant to Bupivacaine did not show significant difference in onset and peak of sensory blockade but Dexmedetomidine provided prolonged duration of sensory blockade and postoperative analgesia as compared to Clonidine group.